Navigating Through the COVID-19 Crisis: A Case Study of Starbucks - Daisy Mui Hung Kee; Muhammad Faheem; Sarah Ammar Lutf Al-Anesi; Mohd Yusoff Imran; Muhammad Hazrul; Ahmad Amiruddin Khairi (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
The purpose of this study is to examine the impact of the COVID-19 pandemic on the world's most famous coffeehouse chain, Starbucks Corporation. Starbucks has a large number of loyal customers; it makes Starbucks qualify as the best object for this study. By the end of 2020, Starbucks has more than 30,000 locations worldwide in more than 80 countries. The COVID-19 pandemic struck Starbucks ' business, forcing the company to looking for new strategies and alternatives to run its business efficiently. This study was built on data collected. There are 100 customers participated in the survey. Discussion and recommendations are presented.